Pelatihan Dasar Kewaspadaan Bencana dan Evakuasi Mandiri di Pondok Modern Muhammadiyah Pakusari Kabupaten Jember - Bakhtiyar Hadi Prakoso; Gandu Eko Julianto Suyoso; Mudafiq Riyan Pratama; Muhammad Yunus; Angga Rahagiyanto (Indonesian Journal Publisher, 2020)
Jember Regency is not immune from the risk of disasters. Information released by BPBD of Jember Regency, in 2018 there have been 224 disasters. This figure has increased more than 100% from the number of events in 2017. Efforts to reduce the risk of existing disasters and prevent new risks can be done by increasing the resilience of the community. From this background the writer through community service activities held a basic training on disaster alert at the Muhammadiyah Modern Pakusari Pondok. In the training the material will be delivered with lectures and demonstrations. With this training the insights of the participants will increase, especially in the field of disaster alertness. In addition participants were also trained to evacuate themselves against the earthquake disaster